2023
DOI: 10.1017/s0022377823000922
|View full text |Cite
|
Sign up to set email alerts
|

Fast correlation heating in moderately coupled electron–ion plasmas

Thomas E. Foster,
Henry Fetsch,
Nathaniel J. Fisch

Abstract: If the electrons in a plasma are suddenly heated, the resulting change in Debye shielding causes the ion kinetic energy to quickly increase. For the first time, this correlation heating, which is much faster than collisional energy exchange, is rigorously derived for a moderately coupled, electron–ion plasma. The electron–ion mass ratio is taken to be the smallest parameter in the Bogoliubov–Born–Green–Kirkwood–Yvon hierarchy, smaller even than the reciprocal of the plasma parameter. This ordering differs from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 101 publications
(193 reference statements)
0
1
0
Order By: Relevance
“…DIH is not a new phenomenon. It has been studied in great detail in ultracold neutral plasmas [30][31][32][33] and more recently, fusion plasmas [34]. However, it has now been shown that DIH is also expected to occur in atmospheric pressure plasmas [12].…”
Section: Strong Coupling and Dihmentioning
confidence: 99%
“…DIH is not a new phenomenon. It has been studied in great detail in ultracold neutral plasmas [30][31][32][33] and more recently, fusion plasmas [34]. However, it has now been shown that DIH is also expected to occur in atmospheric pressure plasmas [12].…”
Section: Strong Coupling and Dihmentioning
confidence: 99%